Comparative transcriptome analysis reveals the growth and development in larval stages of the swimming crab Portunus trituberculatus - Chen, Jiameng; Chen, Xiayue; Mu, Changkao; Wang, Chunlin; Ye, Yangfang; Li, Ronghua; Song, Weiwei; Shi, Ce; Liu, Lei; Wang, Huan (Frontiers in Marine Science, 2023)
Portunus trituberculatus, an economically important marine crab that was widely distributed along the coast of China, has been in short supply of high-quality crab seedlings in recent years. The larval development of P. trituberculatus is regulated by numerous biological processes at different biological levels, particularly regarding gene expression during the larval development process. Understanding the changes in these critical genes can help further regulate these biological processes to increase crab seedlings’ survival and improve crab quality. In this study, the molecular mechanisms of morphological and physiological changes in larval stages of P. trituberculatus were investigated using DNA microarrays. A total of 109,533 unigenes were obtained, of which 16 genes were differentially expressed during the whole development stages with evident timeliness. The enrichment analysis and comparison of differentially expressed genes (DEGs) showed three types of physiological activities, chitin development, energy metabolism, and neuroendocrine development. The physiological activities were evident in the early development of P. trituberculatus, especially at the Z4-M stage, which is crucial for the growth and development of crab larvae. These DEGs, cuticle proteins, retinol dehydrogenase (RDHs), Juvenile Hormone Epoxide Hydrolase (JHEH), and other vital genes were differentially expressed at the Z4-M stage. Moreover, the insulin-like androgenic gland (IAG), which was reported to be associated with sex differentiation, was highly expressed in the megalopa stage, indicating that the gender differentiation divide may occur at the beginning of this stage. Overall, this research provides a theoretical basis for the development of the swimming crab larvae, which could contribute to the artificial growing seedlings technology of P. trituberculatus.